The efficacy of irinotecan, paclitaxel, and oxaliplatin (IPO) in relapsed germ cell tumours with high‐dose chemotherapy as consolidation: a non‐cisplatin‐based induction approach. (13th June 2015) - Badreldin, Waleed; Krell, Jonathan; Chowdhury, Simon; Harland, Stephen J.; Mazhar, Danish; Harding, Victoria; Frampton, Adam E.; Wilson, Peter; Berney, Daniel; Stebbing, Justin; Shamash, Jonathan
Abstract : Objectives: To determine the outcome of an expanded cohort of patients with relapsed germ cell tumours (GCTs) treated with a salvage chemotherapy regimen consisting of irinotecan, paclitaxel and oxaliplatin (IPO) and assess the role of IPO as an alternative to standard cisplatin‐based chemotherapy regimens in this setting. Patients and Methods: The results of 72 consecutive patients were reviewed retrospectively. IPO was used either as a second‐line treatment (29 patients), of which 20 patients subsequently received high‐dose chemotherapy (HDCT), or third‐line (43), of which 32 patients proceeded to HDCT. Results: The 2‐year progression‐free survival (PFS) and 3‐year overall survival (OS) rates for the whole cohort were 30.2% (95% confidence interval [CI] 17.3–40.5%) and 33.4% (95% CI 20.1–43.8%), respectively. Complete remission was achieved in 3%, marker‐negative partial response (PR) in 41%, marker‐positive PR in 18%, stable disease in 17% and progressive disease in 20%. In the second‐line setting, the 2‐year PFS rate was 43.5% (95% CI 21.7–60.8%) and 3‐year OS 49.1% (95% CI 24.2–65.1%). In the third‐line setting, the 2‐year PFS rate was 21.0% (95% CI 9.5–35.4%) and the 3‐year OS rate was 23.9% (95% CI 11.7–38.2). According to the current international prognostic factor study group criteria for first relapse for the high‐ and very high‐risk group the 2‐year PFS rates were 50% and 30%, respectively. There were two treatment‐related deaths from IPO, and four from HDCT. Grade 3 or 4 toxicities included neutropenia (35%), thrombocytopaenia (18%), infection (15%), diarrhoea (11%) and lethargy (8%). Conclusions: IPO offers an effective, well‐tolerated, non‐nephrotoxic alternative to cisplatin‐based salvage regimens for patients with relapsed GCTs. It appears particularly useful in high‐risk patients and for those in whom cisplatin is ineffective or contra‐indicated.